Pemberdayaan Masyarakat dalam Meningkatkan Pengetahuan dan Pemanfaatan Bahan Alam Menjadi Sediaan Antiseptik dalam Pencegahan Covid-19 - Haflin Haflin; Agusriani Agusriani; Lailan Azizah (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
The emergence of the corona virus has shocked the whole world, including Indonesia. This virus has claimed many victims every day. Many aspects of people's lives are affected, especially the local economy, especially the residents of Muara Jambi Village, Maro Sebo District, Muaro Jambi Regency. Corona virus can be prevented, including by washing hands with soap (Handwash) or by spraying Handsanitizer. This handwash and hand sanitizer can be made using natural ingredients including pineapple peel extract and sungkai leaf extract. The purpose of this service is to increase public knowledge regarding the use of natural materials for the manufacture of hand sanitizers and handwashes, as well as to make preparations directly. From this service activity, it is known that there is an increase in community knowledge, reaching 98.05%. The community is also able to make hand sanitizer and handwash preparations from natural ingredients. The conclusion is the increasing public knowledge of some information related to the use of natural materials for the manufacture of hand sanitizer and handwash and the community can utilize and process natural materials that have potential as an alternative in making hand sanitizer and handwash